Physical properties of near-Earth asteroid (2102) Tantalus from multiwavelength observations. Issue 3 (4th July 2022) - Rożek, Agata; Lowry, Stephen C; Rozitis, Benjamin; Dover, Lord R; Taylor, Patrick A; Virkki, Anne; Green, Simon F; Snodgrass, Colin; Fitzsimmons, Alan; Campbell-White, Justyn; Sajadian, Sedighe; Bozza, Valerio; et al.
ABSTRACT: Between 2010 and 2017, we have collected new optical and radar observations of the potentially hazardous asteroid (2102) Tantalus from the ESO NTT and Danish telescopes at the La Silla Observatory, and from the Arecibo planetary radar. The object appears to be nearly spherical, showing a low-amplitude light-curve variation and limited large-scale features in the radar images. The spin-state is difficult to constrain with the available data; including a certain light-curve subset significantly changes the spin-state estimates, and the uncertainties on period determination are significant. Constraining any change in rotation rate was not possible, despite decades of observations. The convex light curve-inversion model, with rotational pole at λ = 210° ± 41° and β = −30° ± 35°, is more flattened than the two models reconstructed by including radar observations: with prograde (λ = 36° ± 23°, β = 30° ± 15°), and with retrograde rotation mode (λ = 180° ± 24°, β = −30 ± 16°). Using data from WISE, we were able to determine that the prograde model produces the best agreement in size determination between radar and thermophysical modelling. Radar measurements indicate possible variation in surface properties, suggesting one side might have lower radar albedo and be rougher at the centimetre-to-decimetre scale than the other. However, further observations are needed to confirm this. Thermophysical analysis indicates a surface covered in fine-grained regolith, consistent with radar albedo, and polarisation ratio measurements. Finally, geophysical investigation of the spin-stability of Tantalus shows that it could be exceeding its critical spin-rate via cohesive forces.